Liver apparent diffusion coefficient repeatability with individually predetermined optimal cardiac timing and artifact elimination by signal filtering. Issue 5 (13th November 2015) - Metens, Thierry; Absil, Julie; Denolin, Vincent; Bali, Maria Antonietta; Matos, Celso
Abstract : Purpose: To prospectively assess liver ADC (apparent diffusion coefficient) repeatability from cardiac‐triggered diffusion‐weighted images obtained with an individually predetermined optimal cardiac time window minimizing cardiac‐related effects and to evaluate a signal filtering method aimed at artifact elimination. Materials and Methods: After Institutional Review Board approval and written informed consent, eight healthy volunteers underwent four repetitions of respiratory‐triggered diffusion‐weighted sequences (3T, b: 0, 150, 500 s/mm 2 ) without (RTnoCT, 51 sec) and with individually optimized cardiac triggering (RTCT, 306 sec). The optimal cardiac delay was individually predetermined using a 5‐second breath‐hold sequence. Monoexponential liver ADC and left‐to‐right‐liver ADC ratio were computed from region of interest (ROI) signal measurements (two independent readers). A filtering method, excluding signal intensities lower than the mean intensity at fixed b‐value, provided ADC recalculation. Limits‐of‐agreement (LOAs) from 95% confidence intervals for differences across the four repetitions provided the variability range. Results: For Reader 1 (Reader 2), left‐to‐right‐liver ADC ratios were significantly higher in RTnoCT 1.51 (1.52) than in RTCT 1.12 (1.15), P = 0.012 ( P = 0.017). Respectively for RTnoCT and RTCT: left liver LOAs were ±835 (±775), ± 315 (±369) 10 ‐6 mm 2 /s; right liver LOAs were ±392 (±445), ± 172 (±140) 10 ‐6 mm 2 /s: LOAs were larger in the left than in the right lobe (both P < 0.001). After filtering, left liver ADC LOAs narrowed to ±650 (±367) 10 ‐6 mm 2 /s, P = 0.17 ( P < 0.001); ± 152 (±208) 10 ‐6 mm 2 /s (both P < 0.002) and left‐to‐right‐liver ADC ratio decreased to 1.28 (1.20), P = 0.017 ( P = 0.012); 1.09 (1.08), P = 0.106 ( P = 0.105). Conclusion: Compared to noncardiac‐triggered acquisitions, individually optimized cardiac‐triggered acquisitions improved ADC repeatability in both liver lobes and reduced ADC differences between left and right liver. Left liver ADC repeatability was further improved after signal filtering. J. Magn. Reson. Imaging 2016;43:1100–1110.